Hemodynamic rounds: Can we mimic a temporary pulmonary artery band in catheterization laboratory in corrected transposition of great arteries with severe tricuspid regurgitation? - Avinash Anantharaj; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2018)
Right ventricular (RV) geometry is altered by septal shift after pulmonary artery banding. This may reduce tricuspid regurgitation (TR) and improve ventricular function in patients with corrected transposition of great arteries and systemic right ventricle. However, banding is risky in sick patients with severe RV failure. There are no predictive models in clinical practice to test this septal shift hypothesis before a risky surgery. A transcatheter model to mimic a pulmonary artery band is presented in corrected transposition of great arteries with failing right ventricle and severe TR.